Supervisory conversations on rigour and interpretive research - Whiteley, Alma (Emerald Group Publishing Limited, 2012)
Purpose: The purpose of this paper is to provide a comprehensive narrative account of supervisory conversations with doctoral students. They include providing knowledge and experience about the nature of qualitative and quantitative approaches and their respective histories and rigour requirements. Design/methodological/approach: An introduction reveals the complexity, debates and dialectics that are engaged with during the doctoral supervisory process. Two design issues are discussed. One is research design; the other is supervisor method. Findings: Rigour in interpretive research is distinctive, linked to its characteristics and the unique role of the researcher as an instrument of data collection, conscious of the need to give voice to respondents and preserve their authentic responses. The audit trail is a centrepiece for both rigour and the reflection, reflexivity necessary to address ongoing biases, decisions and dilemmas. Research limitations/implications: Supervisory conversations are dynamic but there is a core, a set of initial conditions and these relate to the ethics and integrity of the doctoral student and the supervisor. Originality/value: The paper penetrates the social space where supervisors and doctoral students interact. Within the text, “advice” and seminal ideas are presented from literature and the supervisor's experience that will inform researchers and demonstrate a supervisor method.